Psychology in sports coaching theory and practice - Nicholls, Adam R. (London Routledge, Taylor & Francis Group, 2017)
Some of the most effective coaches understand the fundamentals of sport psychology, which include interacting effectively with athletes, creating the optimal environment, assessing the psychological needs of their athletes, and even providing them with the mental training required to maximise performance. Fully revised and updated, the second edition of Psychology in Sports Coaching: Theory and Practice clearly and accessibly introduces the principles and practice of sport psychology in the context of the coaching process. Drawing on the very latest research and theory, the book introduces the psychological tools and techniques that coaches can use to get the best performances out of their athletes.
Part I: Providing Sport Psychology as a Coach -- 1. Introduction to Sport Psychology, Ethics, Referrals, and the HCPC -- Part II: Identifying the Psychological Needs of Athletes -- 2. Conducting Intake Interviews -- 3. Using Questionnaires to Assess the Needs of Athletes -- Part III: Facilitating Awareness -- 4. Goal Setting -- 5. Performance Profiling -- Part IV: Coaching Different Populations -- 6. Coaching Children -- 7. Coaching Adolescents -- 8. Coaching Adults -- 9. Coaching Athletes with Learning Disabilities -- 10. Providing Psychological Support to an Injured Athlete -- Part V: Relationships, Support, and Influence within Coaching -- 11. The Coach-Athlete Relationship -- 12. Understanding and Building Team Cohesion -- 13. Socially Supporting Athletes Effectively -- 14. Enhancing Motivation among Athletes -- 15. Creating the optimal motivational climate -- 16. Applying Self-Determination Theory to Enhance Coaching Practice -- 17. Promoting Anti-Doping Attitudes Among Athletes -- Part VI: Developing Mental Skills among Athletes -- 18. Mental Imagery -- 19. Mental Toughness Training -- 20. Maximising Sport Confidence -- 21. Coping Effectiveness Training -- 22. Enhancing Challenge States and Minimising Threat States among athletes -- 23. Mindfulness Based Stress Reduction Training -- 24. Preventing Choking Under Pressure in Sport -- References
Includes bibliographical references (pages [247]-274) and index.
Keywords: Coaching (Athletics) -- Psychological aspects; Sports -- Psychological aspects